Brivaracetam and topiramate serum levels during pregnancy and delivery: a case report and a review of literature - Wiebke Hahn; Leona Möller; Katja Menzler; Tobias Poeplau; Uwe Wagner; Susanne Knake (Neurological Research and Practice, 2024)
Abstract Background An increasing use of newer antiseizure medication (ASM) such as SV2A ligand brivaracetam is observed. However, data on newer antiseizure medication and therapeutic drug monitoring during pregnancy is scarce. Methods Therapeutic drug monitoring of brivaracetam (BRV) and topiramate (TPM) serum levels were performed during pregnancy, delivery and in the umbilical cord blood at delivery in a 34-year-old female patient with severe drug-resistant epilepsy. Results During pregnancy, the serum levels of brivaracetam and topiramate remained stable. At 39th week of pregnancy, the patient gave birth to a healthy daughter. 1.5 h after the last ASM intake, the penetration rate measured in umbilical cord blood was 45% lower for BRV and 35% lower for TPM. Conclusions While the pharmacokinetics of topiramate are well known and its use during pregnancy should only be undertaken under special circumstances, there have been few studies on newer ASM in pregnancy such as brivaracetam. Based on our results and other case reports of BRV use during pregnancy, further studies are necessary to confirm its pharmacokinetics and safety during pregnancy.